2015
DOI: 10.1007/s00256-015-2230-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasound of peripheral nerves in systemic sclerosis: a pilot study of computer-aided quantitative assessment of nerve density

Abstract: In lcSSc patients, nerve density was reduced, especially in the symptomatic group, compared to control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The evidence from these studies suggests that CTS occurring concomitantly to SSc is also associated with ultra sonographically-detectable morphological alterations of the median nerve. Specifically, patients with SSc presented with larger CSA, higher transverse diameters, and higher flattening ratios of the median nerve than healthy controls [46] and had lower ratio of fascicular to non-fascicular structures within the nerve [47]. These findings are consistent with the ultrasonographic observations of patients with CTS of other aetiology, suggesting that peripheral neuropathy in SSc might develop in a compression mechanism.…”
Section: Peripheral Neuropathy In Systemic Sclerosissupporting
confidence: 71%
“…The evidence from these studies suggests that CTS occurring concomitantly to SSc is also associated with ultra sonographically-detectable morphological alterations of the median nerve. Specifically, patients with SSc presented with larger CSA, higher transverse diameters, and higher flattening ratios of the median nerve than healthy controls [46] and had lower ratio of fascicular to non-fascicular structures within the nerve [47]. These findings are consistent with the ultrasonographic observations of patients with CTS of other aetiology, suggesting that peripheral neuropathy in SSc might develop in a compression mechanism.…”
Section: Peripheral Neuropathy In Systemic Sclerosissupporting
confidence: 71%
“…In this study, we reported that the inside-epineurium method was more reliable than the outside-epineurium method in measuring the nerve CSA due to its higher intra- and inter-rater reliability. In recent years, with advancements in US technology, most high resolution US machines are able to delineate the ultrastructure of the peripheral nerves ( 24 ). The echotexture of nerve fascicles are hypoechoic, whereas the surrounding connective tissues like epineurium and perineurium appear hyperechoic ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that visualized the median nerve in SSC were not about the elasticity of the nerve. The median nerve area, diameter and flattening ratio were significantly affected in patients with SSC [ 8 ] and the ratio between the fascicular and non-fascicular structure of the median nerve was decreased [ 17 ]. This is the first study to actually document an increase in the stiffness of the median nerve in patients with SSC.…”
Section: Discussionmentioning
confidence: 99%